Green banking initiatives: assessing Prime Bank Limited's sustainability efforts in Bangladesh - Neha, Fauzia Kabir (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.